Hemoglobin Level in Cervical Cancer: A Surrogate for an Infiltrative Phenotype. Issue 4 (1st May 2013) - Barkati, Maroie; Fortin, Israël; Mileshkin, Linda; Bernshaw, David; Carrier, Jean-François; Narayan, Kailash
Abstract : Objective: Hemoglobin (Hb) is a prognostic factor in cervical cancer, but the underlying mechanisms remain unknown. In this study, we hypothesized that low Hb level, either before or during radiotherapy (RT), is a surrogate for a more infiltrative and therefore aggressive disease, with uterine corpus invasion and nodal metastases. Methods and Materials: Prospectively collected data of patients with locally advanced cervical cancer treated with curative intent using chemoradiation at a tertiary academic center was reviewed. All eligible patients had a positron emission tomographic scan and pelvic magnetic resonance imaging. Hemoglobin levels before RT and Hb nadir during RT were collected from the medical record. Results: The median follow-up for 263 eligible patients was 38.7 months. Ninety-six patients (36.5%) had both uterine corpus invasion and positron emission tomography–positive nodal disease (C+N+). Patients with pretreatment Hb level of less than 120 g/L were more likely to have C+N+ disease (47%) compared with patients with a high pretreatment Hb level (32%; P = 0.034). The 3-year disease-free survival and overall survival (OS) were significantly lower in the C+N+ group compared with the remaining patients (40.1% vs 76.1%, P < 0.001, and 59.7% vs 83.1%, P < 0.001, respectively). Patients with low Hb nadir were more likely to have a C+N+ disease ( P < 0.001), and low Hb nadir during RT was significantly an indicator of a higher recurrence rate ( P = 0.002) and lower OS ( P < 0.001). In multifactor analysis, statistically significant prognostic factors for OS included histology, high-echelon nodal involvement, tumor volume on magnetic resonance imaging, C+N+ status, and Hb nadir during treatment. Pretreatment Hb level was not an independent prognostic factor. Conclusions: The combination of corpus invasion and nodal metastases is associated with lower Hb level and inferior prognosis. Because C+N+ state is related to tumor growth from early invasion to the time of presentation, it is unlikely that the correction of Hb level during treatment will have a major impact on outcome.